Environmental pollution policy of small businesses in Nigeria and Ghana: Extent and impact - Uchenna Rapuluchukwu Efobi; Tanankem Belmondo; Emmanuel Orkoh; Scholastica Ngozi Atata; Opeyemi Akinyemi; Ibukun Beecroft (African Governance and Development Institute (AGDI), 2018)
This study provides a comprehensive assessment of firms' operation and environmental protection polices in Nigeria and Ghana, where there has been a rising industrial growth amidst low regulatory and institutional frameworks. We analyze the extents to whic h firms' adoption of environmental protection policies affect their performances. We use firm-level data of 842 firms (447 for Nigeria and 395 for Ghana) distributed across different regions of both countries for our descriptive and econometric estimations. We find, among other things, that firms' adoption of internal policies on environmental protection is dismally low in both Nigeria (32 percent) and Ghana (17 percent), with policies focused on reducing solid (38 percent, Nigeria; and 35 percent, Ghana), gaseous (22 percent, Nigeria; and 44 percent, Ghana), and liquid (24 percent, Nigeria; and 14 percent, Ghana) pollution. Training appears to be an important intervention that can help improve firms' adopt ion of such policies. We also found that firms' adoption and implementation of environmental protection policies significantly improve their performance.
Keywords: H32; L25; Q52; Q53; 330; Environment; Green Industrialization; Performance; Pollution; Small Businesses; West Africa